Valorization of Acacia mangium bark for sustainable bio-based wood preservatives: Tannin extraction and boron complexation with additives - Roziela Hanim Alamjuri; Sabiha Salim; Paridah Md Tahir; Lee Seng Hua; Ismawati Palle; Musri Ismenyah; Aizat Ghani
The increasing demand for sustainable and environmentally benign wood protection systems has prompted the exploration of natural polyphenolic compounds such as tannins. This study investigates the valorization of Acacia mangium bark, a plantation byproduct, as a source of condensed tannins for bio-based wood preservatives. Tan-Nin extraction was conducted using three solvent systems: hot water, 70% acetone, and a sulfite-based solution (2% Na2SO3 + 0.5% Na2CO3). Among these, the sulfite- based method demonstrated superior performance, yielding the highest tannin content (56.24%) and purity (Stiasny number = 70), along with elevated phenolic content as measured by UV-Vi's spectrometry. The extracted tannins were complexed with boron-tannin and further modified with various additives—formalin, ϵ-caprolactam, hexamine, and low molecular weight phenol-formaldehyde resin—to enhance leach resistance, gelation time, and viscosity. Among the formulations, BTCHF (boron- tannin-caprolactam-hexamine-formalin) showed the most balanced performance with improved water resistance (40% insoluble matter), moderate viscosity (11.45 cP), and near-neutral pH (6.12). FTIR analysis confirmed the formation of stable crosslinked structures and reduced free –OH groups, indicating successful boron-tannin complex a- Tion. This study provides a novel approach to producing high-performance, renewable wood preservatives from A. mangium bark. The findings highlight the potential of tannin-boron systems as durable and eco-friendly alternatives to synthetic preservatives, supporting sustainable forestry and green construction initiatives in tropical regions.